2016
DOI: 10.5144/0256-4947.2016.51
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, diagnosis and outcome of patients referred to a specialized neurology emergency clinic: prospective observational study

Abstract: BACKGROUNDOrganization and management of neurological emergencies differs among hospitals. Some have specialized neurological emergency rooms (ER).OBJECTIVESThe purpose of this study was to determine the characteristics, diagnosis and outcome of patients referred to a specialized emergency neurology clinic.DESIGNProspective, observational study of consecutive patients presenting between March 2014 and July 2014.SETTINGNeurologicaler of a training and research neuropsychiatric hospital.PATIENTS AND METHODSPatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 14 publications
(13 reference statements)
3
16
1
1
Order By: Relevance
“…Neurological conditions account for 10 to 15% [1] of patients visiting the emergency department (ED), of which 13 to 27.8% are represented by patients with non-traumatic headache as the main complaint [2][3]. These numbers, according to several descriptions represent 0.5 to 2.8% of the emergency visits[4].…”
Section: Introductionmentioning
confidence: 99%
“…Neurological conditions account for 10 to 15% [1] of patients visiting the emergency department (ED), of which 13 to 27.8% are represented by patients with non-traumatic headache as the main complaint [2][3]. These numbers, according to several descriptions represent 0.5 to 2.8% of the emergency visits[4].…”
Section: Introductionmentioning
confidence: 99%
“…Departments that frequently applied for urgent neurological consultation included the intensive care unit (ICU), respiratory medicine, cardiovascular medicine, hematology, and nephrology. At present, it is estimated that about 10% of patients present some neurological manifestations in the previous reports [10][11][12][13]. It has been reported that neurological consultation in the ICU is often urgent consultation, which also suggests that patients have more severe diseases to be managed.…”
Section: Discussionmentioning
confidence: 99%
“…Early intervention by a neurologist is needed to diagnose patients with neurologic symptoms at an early stage and provide accurate initial treatment in the ED. Studies have demonstrated that a dedicated neurologist in the ED reduced the length of stay and the hospital admission rate [ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%